Effectiveness of Yoga therapy for relief of dysmenorrhoea among adolescents of a selected high school in Faridkot (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Adolescence is a period of transition from childhood to adulthood. These are the formative years when maximum amount of physical, psychological and behavioural changes take place. This is the time for them to prepare for understanding greater responsibilities, a time for exploration and widening horizons, and a time to ensure healthy all-round development. Puberty is also a time of behavioural changes when the reproductive capacities get established. The sex hormones secreted during puberty affect the tissues of the body